2014
DOI: 10.1098/rsta.2013.0292
|View full text |Cite
|
Sign up to set email alerts
|

Impact compressive and bending behaviour of rocks accompanied by electromagnetic phenomena

Abstract: It is well known that electromagnetic phenomena are often observed preceding earthquakes. However, the mechanism by which these electromagnetic waves are generated during the fracture and deformation of rocks has not been fully identified. Therefore, in order to examine the relationship between the electromagnetic phenomena and the mechanical properties of rocks, uniaxial compression and three-point bending tests for two kinds of rocks with different quartz content, granite and gabbro, have been carried out at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(34 reference statements)
2
6
0
Order By: Relevance
“…It was observed that the increase in EMR signal amplitude measured for the magnetite ore containing quartz was tenfold that of the ore not containing quartz. Similar results were obtained by other researchers (Wan et al 2008, Kobayashi et al 2014. In particular, the authors of (Kobayashi et al 2014), in their experiment on dynamic compression of rocks, observed that the EMR signal amplitude for gabbro with 2 vol.% quartz content was one sixth of that for granite with 36 vol.% quartz content.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…It was observed that the increase in EMR signal amplitude measured for the magnetite ore containing quartz was tenfold that of the ore not containing quartz. Similar results were obtained by other researchers (Wan et al 2008, Kobayashi et al 2014. In particular, the authors of (Kobayashi et al 2014), in their experiment on dynamic compression of rocks, observed that the EMR signal amplitude for gabbro with 2 vol.% quartz content was one sixth of that for granite with 36 vol.% quartz content.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were obtained by other researchers (Wan et al 2008, Kobayashi et al 2014. In particular, the authors of (Kobayashi et al 2014), in their experiment on dynamic compression of rocks, observed that the EMR signal amplitude for gabbro with 2 vol.% quartz content was one sixth of that for granite with 36 vol.% quartz content. Crystalline quartz inclusions in magnetite ore are randomly distributed over the volume, and this may account for the great spread in EMR signal amplitude from sample to sample in our experiments.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Electromagnetic radiation (EMR) occurring in the rocks under mechanical impact has been studied for many years in many countries around the world [1][2][3][4][5][6][7]. The key motive of these studies is high potential of EMR to be used for predicting geodynamic events such as earthquakes, rock bursts, landslides and others.…”
Section: Introductionmentioning
confidence: 99%